Investigating the Theory of Correspondence between Pedanius Dioscorides and Luqman al-Hakim in Persian Medicine: An Evaluation of Verification Criteria - Nafise Shaabani; Farzaneh Zare; Mohammad Mahdi Parvizi (مجله علوم پزشکی صدرا)
Some traditional medicine texts claim a connection between Pedanius Dioscorides and Luqman al-Hakim. The present study examined the feasibility of accepting this connection and the criteria for confirming or rejecting their correspondence using a documentary method. To this end, in addition to an analytical and historical assessment of the personalities of Luqman al-Hakim and Pedanius Dioscorides, their identities were traced and documented in key traditional Iranian medical texts, including Tohfat ol-Momenin, Gharabadin-e-Salehi, and Makhzan al-Adviyeh. The collected data were then examined, compared, and analyzed. Based on the findings, several historical and medical sources mentioned individuals named Dioscorides and Luqman, four of whom were prominent. The conflation of some reports about these four figures has led to confusion in their identification. The results indicated that the two figures, Dioscorides and Luqman al-Hakim, did not align chronologically. Tracing these individuals in the relevant sources revealed inconsistencies, particularly regarding their personal identities, such as their life span, place of birth or residence, or even their nationality, which casted doubt on the accuracy of the connection between them. Ultimately, it can be concluded that we are likely dealing with another individual who entered the Islamic era under the names Luqman and Dioscorides. Examining the personal identities mentioned in Persian medicine texts can thus enhance our understanding of historical medical records and their interpretation.